2020
DOI: 10.1161/circulationaha.120.050255
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ertugliflozin on Heart Failure–Related Events in Patients With Type 2 Diabetes Mellitus and Established Atherosclerotic Cardiovascular Disease

Abstract: Background: In patients with type 2 diabetes mellitus (T2DM), sodium-glucose cotransporter 2 (SGLT2) inhibitors reduce the risk of hospitalization for heart failure (HHF). We assessed the effect of ertugliflozin on HHF and related outcomes. Methods: VERTIS CV, a double-blind, placebo-controlled trial, randomized patients with T2DM and atherosclerotic cardiovascular (CV) disease to once-daily ertugliflozin 5 mg, 15 mg or placebo. Prespecified secondary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(184 citation statements)
references
References 26 publications
1
173
0
10
Order By: Relevance
“…This included three HF‐specific trials (DAPA‐HF, EMPEROR‐Reduced, and SOLOIST‐WHF) 6–8 and four cardiovascular outcome trials: CANVAS (CANagliflozin cardioVascular Assessment Study), 3 EMPA‐REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients), 4 DECLARE‐TIMI 58 (Multicenter Trial to Evaluate the Effect of Dapagliflozin on the Incidence of Cardiovascular Events), 5 and VERTIS‐CV (eValuation of ERTugliflozin effIcacy and Safety CardioVascular outcomes trial) 21 . HF patient data from the cardiovascular outcome trials were available from published post hoc studies 22–25 . Although the recently published SCORED (Cardiovascular and Renal Events in Patients With Type 2 Diabetes and Moderate Renal Impairment Who Are at Cardiovascular Risk) trial did not report outcome data of patients with baseline HF separately, 26 the authors of this trial presented a pooled analysis of the SOLOIST‐WHF and SCORED trials at the American Heart Association 2020 conference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included three HF‐specific trials (DAPA‐HF, EMPEROR‐Reduced, and SOLOIST‐WHF) 6–8 and four cardiovascular outcome trials: CANVAS (CANagliflozin cardioVascular Assessment Study), 3 EMPA‐REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients), 4 DECLARE‐TIMI 58 (Multicenter Trial to Evaluate the Effect of Dapagliflozin on the Incidence of Cardiovascular Events), 5 and VERTIS‐CV (eValuation of ERTugliflozin effIcacy and Safety CardioVascular outcomes trial) 21 . HF patient data from the cardiovascular outcome trials were available from published post hoc studies 22–25 . Although the recently published SCORED (Cardiovascular and Renal Events in Patients With Type 2 Diabetes and Moderate Renal Impairment Who Are at Cardiovascular Risk) trial did not report outcome data of patients with baseline HF separately, 26 the authors of this trial presented a pooled analysis of the SOLOIST‐WHF and SCORED trials at the American Heart Association 2020 conference.…”
Section: Resultsmentioning
confidence: 99%
“…This included three HF-specific trials (DAPA-HF, EMPEROR-Reduced, and SOLOIST-WHF) [6][7][8] and four cardiovascular outcome trials: CANVAS (CANagliflozin cardioVascular Assessment Study), 3 21 HF patient data from the cardiovascular outcome trials were available from published post hoc studies. [22][23][24][25] Although the recently published SCORED (Cardiovascular and Renal Events in Patients With Type 2 Diabetes and Moderate Renal Impairment Who Are at Cardiovascular Risk) trial did not report outcome data of patients with baseline HF separately, 26 the authors of this trial presented a pooled analysis of the SOLOIST-WHF and SCORED trials at the American Heart Association 2020 conference. Whenever possible, the pooled findings from these trials were used in our analysis.…”
Section: Search Results Study Characteristics and Baseline Demograpmentioning
confidence: 99%
“…1. HF patient data from cardiovascular outcome trials were available from published post-hoc studies [22,23].…”
Section: Search Resultsmentioning
confidence: 99%
“…Due to the significant reduction of CV risk with empagliflozin, dapagliflozin, and canagliflozin in patients with T2DM, these benefits were once considered as class effects of SGLT2 inhibitors ( 135 ). However, recent studies showed inconsistent results, suggesting that SGLT2 inhibitors may have heterogeneity ( 136 ).…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%